The Days of Bowing are Gone: Adivasis in South Indian Movies 2022 (Indian Journal of Mass Communication and Journalism (IJMCJ), 2024)
Our nation needs an environment where everyone takes pride in becoming a stakeholder in nation-building and chalking out the future course of our national history. However, the irony is that the real stakeholders and the key figures of our nation-building are still at their tapestry end. People accepted the normalization of Dalit or Tribal discrimination based on various grounds. The influence of the media can have a significant role in this process. In recent decades, movies have showcased a stereotypical representation of tribes and Dalits. However, a whole new group of South Indian film-makers is now trying to alter the way movies are made and seen in India. Their movies showcase diverse voices, experiences, and perspectives, influencing how we perceive and engage with our popular culture. When most film-makers are fascinated by the commercial viability of a film, for them the film makes matters more. Their works are not only for art’s sake but also for life’s sake. Because movies have the power to normalize certain behaviours, attitudes, or beliefs, making them seem more acceptable to the mainstream of society. South Indian movies like Kantara, Jigarthanda DoubleX, and Jai Bheem come in touch with the social reality of discrimination faced by the people who belong to the lower sections of society. This paper entitled ‘The Days of Bowing Are Gone: Adivasis in South Indian Movies 2022’, tries to explore changing views and perspectives of tribal characters in popular South Indian Cinema in 2022 with special reference to the movies Sembi (Tamil) and Pada (Malayalam).